Hayan na si kidlat - Molina, Russell (Chikiting books, 2013)
"Biboy is as fast as lightning! Swiftly, he goes around and seems to suddenly pop out of nowhere, everywhere,, at one! He can move so quickly,, it's almost as if he's flying. here comes Kidlat! But there's one thing which can make even a boy as fast as Kidlat powerless. What is Biboy weakness? With lighthearted prose and cheerful characters, Hayan na si Kidlat! reveals the mystery of the boy who moves (almost) at the speed of light."